Fetal Cleft Lip/Palate Surgery: End of a Dream?. (3rd July 2016) - Ozturk, Sinan; Karagoz, Huseyin; Zor, Fatih; Inangil, Gökhan; Kara, Kemal
ABSTRACT: Recognition that a fetus can scarlessly heal in intrauterine life led to various animal studies in the mid 1980s exploring the possibility of fetal cleft lip/palate surgery. The idea of scarless cleft repair seemed like a possible dream after the promising results from the early animal studies. In this review, we analyze the progress made in the 30 years since our first experience with animal models.